2023
DOI: 10.1002/cjoc.202300234
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progresses on Dopant‐Free Organic Hole Transport Materials toward Efficient and Stable Perovskite Solar Cells

Abstract: Comprehensive SummaryAs the third generation new battery, the power conversion efficiency (PCE) of metal halide perovskite solar cells (PSCs) have increased from 3.8% in 2009 to 25.8% currently certified, which fully show that they have great research value and development prospect. As one of the main components of high‐efficiency PSCs, hole transport materials (HTMs) play an important role in extracting and transporting holes and inhibiting charge recombination. However, commonly used HTMs require doping, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 126 publications
0
2
0
Order By: Relevance
“…The integrated photocurrent densities obtained from the external quantum efficiency (EQE) curves were 23.5, 24.0 and 24.2 mA cm −2 for DTTP‐ThC6, DTTP‐ThSO and Spiro‐OMeTAD based devices, respectively, which were well in agreement with the measured J sc values (Figure 6c). To the best of our knowledge, the PCE, especially the FF are among the highest values for the dopant‐free small molecular/polymeric HTMs‐based n‐i‐p PSCs reported so far (Figure 6d, Table S5) [6a] …”
Section: Resultsmentioning
confidence: 80%
“…The integrated photocurrent densities obtained from the external quantum efficiency (EQE) curves were 23.5, 24.0 and 24.2 mA cm −2 for DTTP‐ThC6, DTTP‐ThSO and Spiro‐OMeTAD based devices, respectively, which were well in agreement with the measured J sc values (Figure 6c). To the best of our knowledge, the PCE, especially the FF are among the highest values for the dopant‐free small molecular/polymeric HTMs‐based n‐i‐p PSCs reported so far (Figure 6d, Table S5) [6a] …”
Section: Resultsmentioning
confidence: 80%
“…46–48 Recently, several reviews concerning organic dopant-free HTMs have been published, and the structure–property correlation has been well documented. 49–51 Generally, it is believed that the HTMs with deep highest occupied molecular orbital (HOMO) energy levels and high hole mobility contribute to open-circuit voltage ( V OC ), short-circuit current density ( J SC ) and fill factor (FF), respectively. However, it was found that there is not strong relationship between these two material properties and the photovoltaic parameters of devices (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] Conjugated polymers (CPs) have long-range conjugation chains, benefiting carriers transport through the intermolecular jump and intra-molecular transfers to obtain high hole mobility without doping. [20][21][22][23][24] Electron donor (D)-electron acceptor (A) type CPs are the promising candidates as dopant-free HTMs for PVSCs, [25] due to their intermolecular and intramolecular chargetransfers (ICT). [26][27][28] The current study on D-A polymeric HTMs focuses on the chemical modification of D and A units in substituents, [29,30] π-bridge, [31] and conjugated rings.…”
Section: Introductionmentioning
confidence: 99%